The Needs for Official Sharia Compliance Audit Institution to Protect Customers of Islamic Banking: an Application through Ḥisba - Bharudin Che Pa; Mohd Roslan Mohd Nor; Sanusi Abdul Manaf (International Journal of Nusantara Islam, 2017)
The emergence of Islamic banking system in most banks in Malaysia nowadays bring a new era in Malaysian banking industry. This article discusses the needs for official sharia compliance audit institution to protect customers of Islamic banking. By using literature studies, this article concludes that one of the contributing factors which lead people to adopt Islamic banking system is their awareness of the serious and intolerable prohibition of riba. Some of the ways to ensure customers are well protected are to establish ḥisba institution as Sharia compliance audit body. The establishment of ḥisba institution allows it to stop the violation of Allah’s prohibition and protect the society. With the establishment of the institution, it can play an important role to solicit advice and to monitor performance so that the banks operate strictly as according to the Islamic regulations.